METHOD OF INTESTINAL DECOMPRESSION IN TREATMENT OF RECTAL CANCER COMPLICATED BY INTESTINAL OBSTRUCTION - E. V. Kalinin; E. A. Suleimanov (Сибирский онкологический журнал)
Stoma surgery in patients with obstructive rectal cancer is not a rare case. That is why we studied a possibility of conservative treatment with large bowel obstruction (LBO) using the method of endoscopic recanalization. Material and methods. We enrolled 117 rectal cancer patients with acute or partial LBO. Fifty-eight patients were treated with endoscopic recanalization of lumen. After achieving intestinal decompression, the patients received preoperative chemoradiotherapy (40–60 Gy, tegafur 300 mg/м2, 1–28 days) followed by surgery. The control group consisted of 59 patients who were treated with surgery followed by chemoradiotherapy. Results. Decompression was successful in 48 patients (82.7 %). Partial recanalization was observed in 8 patients, but it was not obstacle to perform chemoradiotherapy. Two patients developed complications (paracolic abscess), requiring unplanned emergency surgery. The frequency of sphincter-preserving surgical procedures was 82.6 % in the study group and 28.8 % in the control group, p<0.001. Conclusion. The proposed method of intestinal decompression allowed the number of sphincter-sparing surgery to be increased without worsening the disease prognosis.